Principle of Least Action in Models and Algorithms of Optimisation States Power System - Lezhniuk, Petro; Teptya, Vira; Komar, Vyacheslav; Rubanenko, Olena (Моделювання, керування та інформаційні технології, 2019)
The possibility and feasibility of applying the principle of least action (PLA) in the optimal control of the states of the electric power system (EPS) is demonstrated. The loss of active power and electricity was taken as the criterion of optimality. The algorithm for determining the optimal state of the EPS is presented. The peculiarity of it is that, in accordance with the PLA, the ideal state of the EPS is first determined, and then parametric constraints are taken into account. The ideal state of the system is characterized by the lowest possible losses, and taking into account active restrictions on the parameters translates the system to the optimal state. The losses increase depending on the heterogeneity of the system in the optimal state of the EPS.